A response to Doole and Marsh (2013) article: methodological limitations in the evaluation of policies to reduce nitrate leaching from New Zealand agriculture. (April 2014) - Daigneault, Adam; Greenhalgh, Suzie; Samarasinghe, Oshadhi
<x xml:space="preserve">Abstract</x> A recent paper by Doole and Marsh (2013), questioned the validity of using the New Zealand Forest and Agriculture Regional Model (NZFARM) for New Zealand agri‐environmental policy analysis. We respond to their critique by clearly describing the model structure, explaining the NZFARM parameterisation, calibration, and validation procedure, and presenting estimates from a series of nutrient reduction policy scenarios to highlight the utility of the model. In doing so, we demonstrate that NZFARM generates logical and intuitive results that can be used for robust agri‐environmental policy decision‐making.